Anti-carbon-deposition organic modified molybdenum-vanadium oxide-loaded montmorillonite catalyst as well as preparation method and application thereof

By organically modifying the montmorillonite catalyst, supporting molybdenum vanadium oxide and ultrasonic dispersion using hydroquinone, the problem of the catalyst prone to carbon deposits in the glycerol dehydration and oxidation reaction is solved, and the long life and high selectivity of the catalyst are achieved.

CN120155245AActive Publication Date: 2025-06-17ZHEJIANG UNIV OF TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510196397.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-21
Publication Date
2025-06-17
Estimated Expiration
2045-02-21

AI Technical Summary

Technical Problem

In the glycerol dehydration and oxidation reaction, the catalyst is prone to carbon deposits, resulting in rapid inactivation, and the existing anti-carbon deposit methods are not effective.

Method used

By organically modifying the montmorillonite catalyst, the specific steps include supporting the molybdenum vanadium oxide on acidified montmorillonite and ultrasonic dispersion using hydroquinone to form a montmorillonite catalyst that is resistant to carbon deposits and organically modified to support the molybdenum vanadium oxide.

Benefits of technology

It effectively prevents the formation of carbon deposits in glycerol catalytic oxidation reaction, extends the service life of the catalyst, and improves the selectivity of the reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005281615960000011
    Figure HDA0005281615960000011
  • Figure HDA0005281615960000012
    Figure HDA0005281615960000012
  • Figure HDA0005281615960000021
    Figure HDA0005281615960000021
Patent Text Reader

Abstract

The invention discloses an anti-carbon-deposition organic modified molybdenum-vanadium oxide-loaded montmorillonite catalyst and a preparation method and application thereof.Hydroquinone is used for organic modification of the molybdenum and vanadium-loaded acidified montmorillonite catalyst, and the obtained catalyst is used for gas-phase glycerol catalytic dehydration oxidation reaction, has good anti-carbon-deposition performance and can be used as a catalyst for gas-phase glycerol catalytic dehydration oxidation reaction. The selectivity of products and the utilization rate of raw materials are improved, and the service life of the catalyst is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a montmorillonite catalyst with anti-coking organic modification and supported molybdenum vanadium oxide, a preparation method thereof, and an application in a catalytic glycerol dehydration oxidation reaction. Background Art

[0002] As one of the main by-products in industrial production of biodiesel, how to convert glycerol into more valuable chemical products is an urgent problem to be solved. Among them, the reaction of catalytic dehydration oxidation of glycerol to high-value organic substances such as acrolein / acrylic acid is a relatively popular research direction; for this reaction, many studies on catalysts have been carried out. Common glycerol dehydration oxidation catalysts include: metal phosphates, metal sulfates, metal oxides, heteropolyacids, zeolites, clay minerals, and solid acid catalysts loaded with redox substances (Chunhui Zhou, Weihua Yu, Dongshen Tong. A montmorillonite-based solid acid catalyst and its application in catalytic selective dehydration of glycerol to acrolein: CN104826657B, 2017). In addition, existing studies have shown that Mo and V are typical active substances for one-step dehydration oxidation of glycerol to acrylic acid (Zixuan Lu, Shuangming Li, Sansan Yu. Research progress on composite metal oxide catalysts for oxidation of glycerol to acrylic acid [J]. Journal of Molecular Catalysis, 2020, 34(05): 484-494). The combination of molybdenum and vanadium can adjust the oxidizing property of vanadium and the acid sites of the carrier, and has a good effect in the catalytic glycerol dehydration oxidation reaction. However, during the reaction process, the catalyst is prone to coking, resulting in rapid deactivation.

[0003] At present, there has been some research on the reasons for coking and the influence of coking on the activity of the catalyst. The acidity, physical structure of the catalyst, and different reaction conditions (such as reaction temperature, water and oxygen content) will all affect the coking intensity of the reaction. Some studies have tried to inhibit the formation of coking by adjusting the acid strength and pore size of the catalyst, but the effect is not obvious. (Chun-Jiang Jia, Yong Liu, Wolfgang Schmidt, An-Hui Lu, Ferdi Schüth. Small-sized HZSM-5 zeolite as highly active catalyst for gas phase dehydration of glycerol to acrolein [J]. Journal of Catalysis, 2010, 269: 71-79.)

[0004] Clay minerals can be organically modified, and organic modification is usually used to improve the loading capacity when other metals are loaded on clay minerals; (Bao Yongsheng. Preparation method of an organically modified kaolin supported nano-palladium catalyst: CN106513052A, 2017.) By organically modifying and loading other substances on the catalyst to participate in and change the reaction process, it may play a positive role in preventing the formation of carbon deposition. Many reported anti-carbon deposition methods basically start from changing the reaction conditions and catalyst components, and there has been no research on applying organic modification to anti-carbon deposition. Summary of the Invention

[0005] The present invention provides an anti-carbon deposition organically modified montmorillonite catalyst loaded with molybdenum and vanadium oxides, its preparation method and application. The catalyst of the present invention can prevent the formation of carbon deposition in the glycerol catalytic oxidation reaction and extend the catalyst life.

[0006] Technical principle: The formation of carbon deposition is due to the generation of free radicals by glycerol in the reaction, and the free radicals initiate condensation reactions, resulting in the generation of macromolecular carbon deposition. Therefore, through organic modification, the catalyst can obtain a certain ability to eliminate free radicals, thereby preventing the formation of carbon deposition precursors.

[0007] The technical solution of the present invention is as follows:

[0008] A preparation method of an anti-carbon deposition organically modified montmorillonite catalyst loaded with molybdenum and vanadium oxides, comprising the following steps:

[0009] Step 1: Natural sodium-based montmorillonite is crushed, ground, sieved, and dried to obtain montmorillonite powder;

[0010] Step 2: Add the montmorillonite powder obtained in Step 1 to an aqueous phosphoric acid solution, heat to 50 - 80 °C, stir for 1 - 6 h, cool to room temperature, centrifuge, wash (with deionized water), and dry to obtain acidified montmorillonite;

[0011] Preferably, the molar ratio of phosphoric acid to montmorillonite is 1:1 - 3:1;

[0012] Preferably, the liquid-solid ratio of the aqueous phosphoric acid solution to montmorillonite is 10:1 - 30:1, mL / g;

[0013] Step 3: Dissolve ammonium molybdate tetrahydrate and ammonium metavanadate in water to obtain a metal loading solution. Add the acidified montmorillonite obtained in Step 2 to the metal loading solution, stir at 60 - 80 °C for 5 - 8 h, then impregnate for 16 - 32 h, then centrifuge and dry, and calcine in a muffle furnace at 400 - 600 °C for 4 - 8 h to obtain acidified montmorillonite loaded with molybdenum and vanadium bimetallic oxides;

[0014] Preferably, the molar ratio of ammonium molybdate tetrahydrate to ammonium metavanadate is 1:1 - 5:1;

[0015] Preferably, the liquid-solid ratio of the metal-loaded solution to the acidified montmorillonite is 10:1 to 30:1, mL / g;

[0016] Step 4: Dissolve hydroquinone in deionized water to obtain a hydroquinone solution. Grind the acidified montmorillonite loaded with molybdenum-vanadium bimetallic oxide obtained in Step 3, add it to deionized water, disperse it evenly by ultrasonic wave, then add the hydroquinone solution, stir at 60-80 °C for 8-12 h, centrifuge, wash (with deionized water), and dry to obtain the montmorillonite catalyst with anti-coking organic modified molybdenum-vanadium oxide;

[0017] Preferably, the mass ratio of hydroquinone to the acidified montmorillonite loaded with molybdenum-vanadium bimetallic oxide is 1:100 to 1:25.

[0018] The present invention relates to a montmorillonite catalyst with anti-coking organic modified molybdenum-vanadium oxide prepared by the above preparation method.

[0019] The montmorillonite catalyst with anti-coking organic modified molybdenum-vanadium oxide of the present invention can be applied to the gas-phase catalytic dehydration oxidation reaction of glycerol.

[0020] The beneficial effects of the present invention are as follows:

[0021] By the method of organic modification of the montmorillonite catalyst, the present invention endows it with the ability of anti-coking during the catalytic dehydration oxidation of glycerol, effectively improving the service life and reaction selectivity of the catalyst, and being suitable for industrial production applications. Description of the Drawings

[0022] Figure 1 : Thermogravimetric analysis diagram of the waste catalyst of HQ-Mo-V MMT prepared in Example 1.

[0023] Figure 2 : Thermogravimetric analysis diagram of the waste catalyst of HQ-Mo-V MMT prepared in Example 2.

[0024] Figure 3 : Thermogravimetric analysis diagram of the waste catalyst of HQ-Mo-V MMT prepared in Example 3.

[0025] Figure 4 : Thermogravimetric analysis diagram of the waste catalyst of comparative Mo-V MMT. Detailed Embodiments

[0026] The present invention will be further described below in conjunction with specific implementation embodiments, and the advantages and features of the present invention will become clearer as the description progresses. However, these embodiments are merely exemplary and do not constitute any limitation to the scope of the present invention. Those skilled in the art should understand that without departing from the gist and scope of the present invention described above and below, modifications or substitutions can be made to the details and forms of the technical solutions of the present invention, but these modifications and substitutions all fall within the protection scope of the present invention.

[0027] In the following examples,

[0028] The sodium-based montmorillonite is from Qingyang County, Anhui Province; phosphoric acid is from Sinopharm Chemical Reagent Co., Ltd.; hydroquinone is from Sinopharm Chemical Reagent Co., Ltd.; ammonium molybdate tetrahydrate and ammonium metavanadate are from Sinopharm Chemical Reagent Co., Ltd.

[0029] Example 1

[0030] Use a mortar to grind the sodium-based montmorillonite into a powder state. After sufficient grinding, pass it through a 100-mesh sieve to obtain montmorillonite powder. Prepare a 1 mol / L H3PO4 solution, and then mix the sodium-based montmorillonite with the 1 mol / L H3PO4 solution to form a 5 wt.% montmorillonite suspension. Stir it in a water bath at 80 °C for 4 h, and then cool it to room temperature. Centrifuge the suspension at a speed of 3000 r / min and wash it with deionized water. If the washed liquid is acidic, continue the centrifugation and washing operations until the washed liquid is neutral. Place the obtained white sediment in an evaporating dish and dry it overnight in an oven at 80 °C to obtain acidified montmorillonite. Accurately weigh 0.0904 g of ammonium molybdate and 0.0146 g of ammonium metavanadate and place them in a 50 mL beaker. Add 20 mL of deionized water and stir at 60 °C until completely dissolved. Weigh 2 g of acidified montmorillonite and add it to the above solution. Stir for 5 h and then impregnate for 24 h. Then place it in an oven at 80 °C for constant-temperature drying for 12 h. Finally, put the dried sample into a muffle furnace at 500 °C and calcine it for 4 h. Obtain a catalyst loaded with molybdenum-vanadium bimetallic oxide. Dissolve 0.02 g of hydroquinone in 100 ml of deionized water at 70 °C to obtain an organic modification reagent. Grind and crush 2 g of the catalyst and add it to 100 ml of deionized water. After ultrasonic treatment for 1 h, add the organic modification reagent; then stir the mixture at 70 °C for 8 hours, then wash and centrifuge it with deionized water, and dry it in an oven at 60 °C for 12 hours to obtain an organically modified montmorillonite catalyst HQ-Mo-V MMT.

[0031] Example 2

[0032] Use a mortar to grind sodium-based montmorillonite into a powder state. After sufficient grinding, pass it through a 100-mesh sieve to obtain montmorillonite powder. Prepare a 1 mol / L H3PO4 solution, and then mix sodium-based montmorillonite with the 1 mol / L H3PO4 solution to form a 5 wt.% montmorillonite suspension. Stir it in a water bath at 80 °C for 4 h, and then cool it to room temperature. Centrifuge the suspension at a speed of 3000 r / min and wash it with deionized water. If the washed liquid is acidic, continue the centrifugation and washing operations until the washed liquid is neutral. Place the obtained white sediment in an evaporating dish and dry it overnight in an oven at 80 °C to obtain acidified montmorillonite. Accurately weigh 0.0904 g of ammonium molybdate and 0.0146 g of ammonium metavanadate and place them in a 50 mL beaker. Add 20 mL of deionized water and stir at 60 °C until completely dissolved. Weigh 2 g of acidified montmorillonite and add it to the above solution. Stir for 5 h and then impregnate for 24 h. Then place it in an oven at 80 °C for constant-temperature drying for 12 h. Finally, put the dried sample into a muffle furnace at 500 °C and calcine it for 4 h to obtain a catalyst loaded with molybdenum-vanadium bimetallic oxide. Dissolve 0.04 g of hydroquinone in 100 ml of deionized water at 70 °C to obtain an organic modification reagent. Grind and crush 2 g of the catalyst and add it to 100 ml of deionized water. After ultrasonic treatment for 1 h, add the organic modification reagent; then stir the mixture at 70 °C for 8 hours, then wash and centrifuge it with deionized water, and dry it in an oven at 60 °C for 12 hours to obtain an organically modified montmorillonite catalyst HQ-Mo-V MMT.

[0033] Example 3

[0034] Use a mortar to grind sodium-based montmorillonite into a powder state. After thorough grinding, pass it through a 100-mesh sieve to obtain montmorillonite powder. Prepare a 1 mol / L H3PO4 solution, and then mix sodium-based montmorillonite with the 1 mol / L H3PO4 solution to form a 5 wt.% montmorillonite suspension. Stir it for 4 h under an 80°C water bath heating, and then cool it to room temperature. Centrifuge the suspension at a speed of 3000 r / min and wash it with deionized water. If the washed liquid is acidic, continue the centrifugation and washing operations until the washed liquid is neutral. Place the obtained white sediment in an evaporating dish and dry it overnight in an 80°C oven to obtain acidified montmorillonite. Accurately weigh 0.0904 g of ammonium molybdate and 0.0146 g of ammonium metavanadate and place them in a 50 mL beaker. Add 20 mL of deionized water and stir at 60°C until completely dissolved. Weigh 2 g of acidified montmorillonite and add it to the above solution. Stir for 5 h and then impregnate for 24 h. Then place it in an 80°C oven for constant-temperature drying for 12 h. Finally, put the dried sample into a muffle furnace at 500°C and calcine it for 4 h to obtain a catalyst loaded with molybdenum-vanadium bimetallic oxide. Dissolve 0.02 g of hydroquinone in 100 ml of deionized water at 70°C to obtain an organic modification reagent. Grind and crush 2 g of the catalyst and add it to 100 ml of deionized water. After ultrasonic treatment for 1 h, add the organic modification reagent; then stir the mixture at 80°C for 12 hours, then wash and centrifuge it with deionized water, and dry it in a 60°C oven for 12 hours to obtain an organically modified montmorillonite catalyst HQ-Mo-V MMT.

[0035] Comparative Example 1

[0036] The montmorillonite catalyst Mo-V MMT was prepared in this example. The difference from Example 1 is that in this example, no subsequent operations were carried out after obtaining the catalyst loaded with molybdenum-vanadium bimetallic oxide, and the others were the same as in Example 1, which will not be elaborated here.

[0037] Performance Test

[0038] The catalysts prepared in the examples and comparative examples were used in the gas-phase catalytic dehydration and oxidation reaction of glycerol. The method is as follows:

[0039] Using a fixed-bed reactor, 0.3 g of the prepared catalyst was taken, uniformly mixed with 1.0 g of quartz sand and loaded into a column. The catalyst was fixed at the reaction position through quartz wool. The reaction used a 20 wt.% glycerol aqueous solution as the reaction raw material, and the feeding rate was 0.1 mL / min. The carrier gas component was air, and the flow rate was 20 mL / min. The temperature of the feeding vaporization chamber was 180 °C, the temperature of the pipeline heat preservation was 160 °C, the temperature of the valve box was 160 °C, the reaction temperature was 320 °C, the temperature of the condenser was 5 °C, and the bed pressure was one standard atmosphere. After the reactor temperature reached 320 °C, the feeding pump was started, and the reaction was ended after 5 h. The catalyst after the reaction was taken out, and the catalyst with carbon deposition was obtained by crushing and sieving. Subsequently, the carbon deposition amount of the catalyst with carbon deposition was analyzed by a thermogravimetric analyzer: it was heated from room temperature to 1000 °C under a N2 atmosphere to obtain a thermogravimetric analysis graph. The thermogravimetric analysis was performed twice on the same sample to ensure the accuracy of the data.

[0040] It can be seen from the thermogravimetric analysis graphs of the examples and the comparative examples that after the glycerol catalytic reaction under the same conditions, the carbon deposition amount in the catalyst without hydroquinone modification was significantly higher than that in the catalyst with hydroquinone modification: the total mass percentage of the carbon deposition content in the waste catalyst without hydroquinone modification was about 12.37%; the total mass percentage of the carbon deposition content in the waste catalyst in Example 1 was about 6.03%; the total mass percentage of the carbon deposition content in the waste catalyst in Example 2 was about 8.55%; the total mass percentage of the carbon deposition content in the waste catalyst in Example 3 was about 6.83%. It can be seen that the catalyst modified by hydroquinone has a stronger anti-carbon deposition effect, can extend the service cycle and life of the catalyst, and has a promoting effect on the development of green and efficient glycerol catalytic reaction catalysts.

Claims

1. A method for preparing a carbon deposition resistant organic modified molybdenum-vanadium oxide loaded montmorillonite catalyst, characterized in that: The steps include: Step 1: natural sodium montmorillonite is crushed, ground, sieved and dried to obtain montmorillonite powder; Step 2: adding the montmorillonite powder obtained in step 1 to a phosphoric acid aqueous solution, heating to 50-80° C. and stirring for 1-6 hours, cooling to room temperature, centrifuging, washing, and drying to obtain acidified montmorillonite; Step 3: dissolving ammonium molybdate tetrahydrate and ammonium metavanadate in water to obtain a metal-loaded liquid, adding the acidified montmorillonite obtained in step 2 to the metal-loaded liquid, stirring at 60-80° C. for 5-8 hours, then immersing for 16-32 hours, centrifuging, drying, and calcining in a muffle furnace at 400-600° C. for 4-8 hours to obtain the acidified montmorillonite loaded with molybdenum-vanadium bimetallic oxide; Step 4: dissolving hydroquinone in deionized water to obtain a hydroquinone solution, grinding the acidified montmorillonite loaded with molybdenum-vanadium bimetallic oxide obtained in step 3 and adding it to deionized water, ultrasonically dispersing it uniformly, then adding the hydroquinone solution, stirring at 60-80° C. for 8-12 hours, centrifuging, washing, and drying to obtain the anti-carbon deposition organically modified montmorillonite catalyst loaded with molybdenum-vanadium oxide.

2. The method for preparing the carbon deposition resistant organic modified molybdenum-vanadium oxide loaded montmorillonite catalyst according to claim 1, characterized in that: In step 2, the molar ratio of phosphoric acid to montmorillonite is 1:1 to 3:

1.

3. The method for preparing the carbon deposition resistant organic modified molybdenum-vanadium oxide loaded montmorillonite catalyst according to claim 1, characterized in that: In step 2, the liquid-to-solid ratio of the phosphoric acid aqueous solution to the montmorillonite is 10:1 to 30:1, mL / g.

4. The method for preparing the carbon deposition resistant organic modified molybdenum-vanadium oxide loaded montmorillonite catalyst according to claim 1, characterized in that: In step 3, the molar ratio of ammonium molybdate tetrahydrate to ammonium metavanadate is 1:1 to 5:

1.

5. The method for preparing the carbon deposition resistant organic modified molybdenum-vanadium oxide loaded montmorillonite catalyst according to claim 1, characterized in that: In step 3, the liquid-to-solid ratio of the metal-loaded liquid to the acidified montmorillonite is 10:1 to 30:1, mL / g.

6. The method for preparing the carbon deposition resistant organic modified molybdenum-vanadium oxide loaded montmorillonite catalyst according to claim 1, characterized in that: In step 4, the mass ratio of hydroquinone to the acidified montmorillonite loaded with molybdenum-vanadium bimetallic oxide is 1:100 to 1:

25.

7. The carbon deposition resistant organically modified molybdenum-vanadium oxide loaded montmorillonite catalyst prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the carbon deposition resistant organically modified molybdenum-vanadium oxide-loaded montmorillonite catalyst as claimed in claim 7 in the catalytic dehydration and oxidation reaction of gas-phase glycerol.

Citation Information

Patent Citations

  • Montmorillonite-based solid acid catalyst and application thereof in catalysis of selective dehydration of glycerin to prepare acraldehyde

    CN104826657A

  • Preparation method of organic modified kaolin-loaded nano-palladium catalyst

    CN106513052A

  • Carbon nanotube chain and production process for the same, target detector, and target detection method

    CN101070154A

  • Phosphoric acid modified montmorillonite loaded tungsten oxide catalyst, preparation method and application

    CN105749939A

  • Catalyst for preparing allyl alcohol from glycerol and preparation method thereof

    CN115709060A